Research action about sexually, STD/aids with nurse teachers from nursing school - Miyasaki, Sandra C.S. (2001)
This study dealt with a research - action in order to check up which problems college nurse teachers have when working subjects as sexuality. STD/Aids with the purpose of developing an educational actiort with them about that as muhipliers agents. For gethering the data we used watchiug technics and individual interview handling them an. open queslioimaire. After analysing lhe data we worked with them through preventing educational action about lhe subject making use of a participating methodology expressed in the from of a dialogue. what allowed us a criticai and reflexive analyses of reality, according to World Health Otgarization 's and Paulo Freir's forecasted references, We researched nurse techers of nursing schools from São Paulo State - Brazil mainly women between 27 and 39 years old, about 10 year wotking expehience in a group of 3 specialist. 4 masters and 2 taking doctorate. We organized lhe data ir charts and the contents were analysed by categories and conceming quality, allowing a beuercomprehension and interpetation of the interviewed people's speeches. We infered that lhe researched nurses revealed a rei ative knowledge about, sexuality, STD/Aids, showing a troublesome. scene for individual and .general public health conceming problems that wam about the importance of integrationg efforts amonf social segments, sharing auitudes in order to develop educational preventing actions on this point. We got to the, conclusion that people have basic anel true idea on the troubles conceming STD/Aids, we know it's very complicated to deal with it. However, there's a general assent about lhe necessity of preparing them beuer so that they can-work with uose affairs.